Phase 1 study of combinatorial sorafenib, G‐CSF, and plerixafor treatment in relapsed/refractory, FLT3‐ITD‐mutated acute myelogenous leukemia patients. Issue 11 (19th August 2020) - Borthakur, Gautam; Zeng, Zhihong; Cortes, Jorge E.; Chen, Hsiang‐Chun; Huang, Xuelin; Konopleva, Marina; Ravandi, Farhad; Kadia, Tapan; Patel, Keyur P.; Daver, Naval; Kelly, Mary A.; McQueen, Teresa; et al.
Abstract: Stroma‐leukemia interactions mediated by CXCR4, CD44, VLA4, and their respective ligands contribute to therapy resistance in FLT3‐ITD‐mutated acute myelogenous leukemia (AML). We conducted a phase 1 study with the combination of sorafenib (a FLT3‐ITD inhibitor), plerixafor (a SDF‐1/CXCR4 inhibitor), and G‐CSF (that cleaves SDF‐1, CD44, and VLA4). Twenty‐eight patients with relapsed/refractory FLT3‐ITD‐mutated AML were enrolled from December 2010 to December 2013 at three dose levels of sorafenib (400, 600, and 800 mg twice daily) and G‐CSF and plerixafor were administered every other day for seven doses starting on day one. Sorafenib 800 mg twice daily was selected for the expansion phase. While no dose‐limiting toxicities (DLT) were encountered in the four‐week DLT window, hand‐foot syndrome and rash were seen beyond the DLT window, which required dose reductions in most patients. The response rate was 36% (complete response (CR) = 4, complete remission with incomplete platelet recovery (CRp) = 4, complete remission with incomplete hematologic recovery (CRi) = 1, and partial response (PR) = 1) for the intention to treat population. Treatment resulted in 58.4 and 47 mean fold mobilization of blasts and CD34 /38‐ stem/progenitor cells, respectively, to the circulation. Expression of the adhesion molecules CXCR4, CD44, and VLA4 on circulating leukemia cells correlated negatively with the mobilization of CD34+/38‐, CD34+/38−/123+ "progenitor" cells (all P ≤ .002). Mass cytometry analysis of sequential samples from two patients demonstrated resistance emerging early on from sub‐clones with persistent Akt and/or ERK signaling. In conclusion, the strategy of combined inhibition of FLT3 kinase and stromal adhesive interactions has promising activity in relapsed/refractory, FLT3‐ITD‐mutated AML, which warrants further evaluation in the front‐line setting.